New advances in leukaemia immunotherapy by the use of Chimeric Artificial Antigen Receptors (CARs): state of the art and perspectives for the near future - Cribioli Elisabetta; Tettamanti Sarah; Pizzitola Irene; Attianese Greta; Marin Virna; Biagi Ettore; Biondi Andrea (BMC, 2011)
Abstract Leukaemia immunotherapy represents a fascinating and promising field of translational research, particularly as an integrative approach of bone marrow transplantation. Adoptive immunotherapy by the use of donor-derived expanded leukaemia-specific T cells has showed some kind of clinical response, but the major advance is nowadays represented by gene manipulation of donor immune cells, so that they acquire strict specificity towards the tumour target and potent lytic activity, followed by significant proliferation, increased survival and possibly anti-tumour memory state. This is achieved by gene insertion of Chimeric T-cell Antigen Receptors (CARs), which are artificial molecules containing antibody-derived fragments (to bind the specific target), joined with potent signalling T-Cell Receptor (TCR)-derived domains that activate the manipulated cells. This review will discuss the main application of this approach particularly focusing on the paediatric setting, raising advantages and disadvantages and discussing relevant perspectives of use in the nearest future.